Human development in Kerala: structure and agency in history - Lieten, G.K. (2002)
The first CPI-led government in Kerala in the late 1950s introduced key policy changes that have since become associated with the Kerala development model. This article makes an attempt to assess the long-term effects of this innovative approach followed, especially in the two crucial sectors of education and land reform. In seeking to map progress in such key human development aspects, it also seeks to establish the role of social mobilisation and in assigning to the key figure of the `Kutiamma' her due place in history. But while the impact of social changes on people remains little documented and rests on extrapolation, this period is also assessed in terms of backward and forward linkages - those societal changes that existed before the CPI's election victory as well as changes brought on by the government's own reform measures that in turn led to further political and social development. - Reproduced.
Keywords: Human development - India - Kerala; Human development